Expert Arguments for Trends of Psychiatric Bed Numbers: A Systematic Review of Qualitative Data - Mundt, Adrian P.; Delhey Langerfeldt, Sabine; Rozas Serri, Enzo; Siebenförcher, Mathias; Priebe, Stefan (Frontiers in Psychiatry, 2021)
Introduction: Mental health policies have encouraged removals of psychiatric beds in many countries. It is under debate whether to continue those trends. We conducted a systematic review of expert arguments for trends of psychiatric bed numbers. Methods: We searched seven electronic databases and screened 15 479 papers to identify expert opinions, arguments and recommendations for trends of psychiatric bed numbers, published until December 2020. Data were synthesized using thematic analysis and classified into arguments to maintain or increase numbers and to reduce numbers. Results: 106 publications from 25 countries were included. The most common themes arguing for reductions of psychiatric bed numbers were inadequate use of inpatient care, better integration of care and better use of community care. Arguments to maintain or increase bed numbers included high demand of psychiatric beds, high occupancy rates, increasing admission rates, criminalization of mentally ill, lack of community care and inadequately short length of stay. Cost effectiveness and quality of care were used as arguments for increase or decrease. Conclusions: The expert arguments presented here may guide and focus future debate on the required psychiatric bed numbers. The recommendations may help policymakers to define targets for psychiatric bed numbers. Arguments need careful local evaluation, especially when supporting opposite directions of trends in different contexts.